2013
DOI: 10.1002/cncr.28450
|View full text |Cite
|
Sign up to set email alerts
|

Reducing time‐to‐treatment in underserved Latinas with breast cancer: The Six Cities Study

Abstract: BACKGROUND The interaction of clinical and patient‐level challenges following a breast cancer diagnosis can be a significant source of health care disparities. Failure to address specific cultural features that create or exacerbate barriers can lead to less‐than optimal navigation results, specifically in Hispanic/Latino women. METHODS To address these disparities, the study leaders in San Antonio, Texas, and 5 other regional partners of the federally‐funded Redes En Acción: The National Latino Cancer Research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 32 publications
2
64
0
Order By: Relevance
“…This, in part, can be attributed to the personal characteristics of the navigators (language spoken, commitment to community, knowledge of cultural values and beliefs, relationships with community and stakeholders) [13]. Overall, the role of the navigators as communication brokers is highly consistent with other navigation studies [12, 27–30,] that view them as valuable assets for helping patients access information, problem-solve, and sift through the myriad logistics of cancer care. Further, we ascribe that patient navigators often work within a number of functional area domains as cogently identified by Willis et al, 2013 (31): professional roles and responsibilities, community resources, patient empowerment, communication, barriers to care/health disparities, education/prevention and health promotion, ethics and professional conduct, cultural competency, outreach, care coordination, psychosocial support services/assessment, and advocacy.…”
Section: Discussionsupporting
confidence: 70%
“…This, in part, can be attributed to the personal characteristics of the navigators (language spoken, commitment to community, knowledge of cultural values and beliefs, relationships with community and stakeholders) [13]. Overall, the role of the navigators as communication brokers is highly consistent with other navigation studies [12, 27–30,] that view them as valuable assets for helping patients access information, problem-solve, and sift through the myriad logistics of cancer care. Further, we ascribe that patient navigators often work within a number of functional area domains as cogently identified by Willis et al, 2013 (31): professional roles and responsibilities, community resources, patient empowerment, communication, barriers to care/health disparities, education/prevention and health promotion, ethics and professional conduct, cultural competency, outreach, care coordination, psychosocial support services/assessment, and advocacy.…”
Section: Discussionsupporting
confidence: 70%
“…Study methods are notable for several advantages, compared to existing navigation studies which are limited by single-site studies [20, 25, 37, 3947]. First, we targeted a racial/ethnically diverse population of vulnerable patients seeking care in safety net settings across the country.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies, however, have shown benefit. Ramirez and colleagues [17] in six city study and Lobb [18] in a multisite program in one state both found a benefit in time to initiation of treatment. Studies by both Castaldi and colleagues [19], and Raj and colleagues found a benefit in completion of guideline recommended treatment.…”
Section: Patient Navigation In Cancer Carementioning
confidence: 94%